Empowering rural family networks: parental support and fertility intentions in China - Feng, Ran; Tan, Yiting; Huang, Denghui (Frontiers in Sustainable Food Systems, 2025)
IntroductionFertility decline in rural China raises concerns for demographic sustainability and gender equity. This study examines whether parental support to reproductive-age adults shapes fertility intentions and through which psychological pathways.MethodsWe analyzed 4,263 reproductive-age respondents from the China Family Panel Studies (CFPS). Parental support was measured along three dimensions—emotional support, caring support (childcare/household help), and economic support. Fertility intentions were the outcome. Depressive symptoms and subjective well-being were specified as mediators. We estimated logistic regressions with controls and conducted mediation analyses to test indirect effects.ResultsEmotional support and caring support were positively associated with fertility intentions. Both effects operated partly through lower depressive symptoms and higher subjective well-being. Economic support showed no robust association. Heterogeneity analyses indicated that caring support had a stronger, compensatory effect among rural-urban migrant families and households in under-resourced areas.DiscussionFindings highlight the role of informal, family-based support, especially emotional and caring support, as empowerment mechanisms that enhance psychological well-being and strengthen reproductive agency. Policies that are gender sensitive and rural inclusive, such as expanding affordable childcare and mental-health resources and recognizing unpaid care, may help reduce structural inequalities and promote equitable, sustainable rural development.